3D Nickel Skeletons as Ultrabroadband Terahertz Absorbers (Adv. Electron. Mater. 10/2021). (11th October 2021) - Yang, Peidi; Dai, Mingcong; Xiong, Hongting; Hao, Sibo; Zhang, Weihao; Zhang, Baolong; Ouyang, Chen; Li, Qiao; He, Feng; Miao, Jungang; Wu, Xiaojun
Abstract : 3D Metal Skeletons In article number 2100626, Xiaojun Wu's group demonstrate for the first time that three‐dimensional metal skeletons can be used as highly efficient, ultrabroadband, cost‐effective, environment friendly, and flexible terahertz and millimeter wave absorption materials. This research provides an opportunity for developing next‐generation terahertz wave absorbing materials and technology, accelerating advanced terahertz technologies towards practical applications.